A Review of the Functional Roles of the Zebrafish Aryl Hydrocarbon Receptors. (25th September 2020) - Shankar, Prarthana; Dasgupta, Subham; Hahn, Mark E; Tanguay, Robyn L
Abstract: Over the last 2 decades, the zebrafish ( Danio rerio ) has emerged as a stellar model for unraveling molecular signaling events mediated by the aryl hydrocarbon receptor (AHR), an important ligand-activated receptor found in all eumetazoan animals. Zebrafish have 3 AHRs—AHR1a, AHR1b, and AHR2, and studies have demonstrated the diversity of both the endogenous and toxicological functions of the zebrafish AHRs. In this contemporary review, we first highlight the evolution of the zebrafish ahr genes, and the characteristics of the receptors including developmental and adult expression, their endogenous and inducible roles, and the predicted ligands from homology modeling studies. We then review the toxicity of a broad spectrum of AHR ligands across multiple life stages (early stage, and adult), discuss their transcriptomic and epigenetic mechanisms of action, and report on any known interactions between the AHRs and other signaling pathways. Through this article, we summarize the promising research that furthers our understanding of the complex AHR pathway through the extensive use of zebrafish as a model, coupled with a large array of molecular techniques. As much of the research has focused on the functions of AHR2 during development and the mechanism of TCDD (2, 3, 7, 8-tetrachlorodibenzo- p -dioxin) toxicity, we illustrate the need to address the considerable knowledge gap in our understanding of both the mechanistic roles of AHR1a and AHR1b, and the diverse modes of toxicity of the various AHR ligands.